Characterization of the supply and value chains of colombian cocoa (2014)
This paper introduces the supply and value chains of the Colombian cocoa agribusiness. For such purpose, we have identified not only the agents, phases, stages and factors influencing the planting and harvesting of the product, but also the chocolate and confection production process, as well as the final consumption. Finally, the national production is described in the context provided by the international market.